Methods and models in statistics : in honour of Professor John Nelder, FRS. - Nelder, John A.; Adams, Niall M., 1968- (Imperial College Press, 2004)
John Nelder is one of today's leading statisticians, having made an impact on many parts of the discipline. This book contains reviews of some of those areas, written by top researchers. It is accessible to non-specialists, and is noteworthy for its breadth of coverage.